(untitled) (PERcursos Linguísticos, 2022)
In this paper, the proposal is to discuss and reflect on Dany-Robert Dufour’s Trinitarian pronominal device, to reflect on its use in the analysis of the literary text. For this, it was used excerpts from the book The Stranger (1942), by Albert Camus, to think about the pronominal reversibility, the "I" and the "you", in the face of the opposition that is established to the "he", in the literary text. Divided into two parts, The Stranger features Meursault, who suffers a twist in his life after committing a murder at the end of the first part of the book. Following this, in the second part, Meursault finds himself increasingly estranged from his place in discourse, outside the reversibility between I-you, as he is relegated to the role of a non-person, the "he". Therefore, the main objective is to show how the absence re-presented in this discursive field of reversibility, can be characterized as a presence of this absent, the "he", from Dufour (2000), in the discursive and intersubjective instance between the speakers I-you, as well as bring a particular point of view to the analysis of the book, showing the character-narrator amid the pronominal alternation established in the work of Camus.